Stellar substructures in the periphery of the Magellanic Clouds with the VISTA hemisphere survey from the red clump and other tracers. Issue 2 (19th April 2021) - El Youssoufi, Dalal; Cioni, Maria-Rosa L; Bell, Cameron P M; de Grijs, Richard; Groenewegen, Martin A T; Ivanov, Valentin D; Matijevĭc, Gal; Niederhofer, Florian; Oliveira, Joana M; Ripepi, Vincenzo; Schmidt, Thomas; Subramanian, Smitha; et al.
ABSTRACT: We study the morphology of the stellar periphery of the Magellanic Clouds in search of substructure using near-infrared imaging data from the Visible and Infrared Survey Telescope for Astronomy Hemisphere Survey. Based on the selection of different stellar populations using the ( J − K s, K s ) colour–magnitude diagram, we confirm the presence of substructures related to the interaction history of the Clouds and find new substructures on the eastern side of the LMC disc, which may be owing to the influence of the Milky Way, and on the northern side of the SMC, which is probably associated with the ellipsoidal structure of the galaxy. We also study the luminosity function of red clump stars in the SMC and confirm the presence of a bi-modal distance distribution, in the form of a foreground population. We find that this bi-modality is still detectable in the eastern regions of the galaxy out to a 10 ○ distance from its centre. Additionally, a background structure is detected in the North between 7 ○ and 10 ○ from the centre that might belong to the Counter Bridge, and a foreground structure is detected in the South between 6 ○ and 8 ○ from the centre that might be linked to the Old Bridge.